Fencing the Flint Hills - Jeff Davidson (Symphony in the Flint Hills, 2017)
Introduction: As the Chisholm trail became the thoroughfare for millions of Texas cattle coming to railheads in Kansas, it initiated economic opportunities in Kansas cattle towns and the countryside surround them. But the increased settlement it spawned only served as obstacles to trail drovers as homesteads with their fences were established.
Keywords: homesteading; Kansas; fencing; building materials; barbed wire; Native Stone Scenic Byway